2016
DOI: 10.4067/s0718-95162016005000070
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of inoculation with arbuscular mycorrhizal fungi to the bioremediation of a copper polluted soil using Oenothera picensis

Abstract: The Bradford-reactive soil protein (BRSP) fraction includes glomalin, a glycoprotein produced by arbuscular mycorrhizal (AM) fungi able to bind some metals, such as copper (Cu), which could promote the bioremediation of Cu-polluted soils. This study aimed to analyze the Cu-binding capacity of BRSP in Oenothera picensis that was inoculated or not inoculated with AM fungi. O. picensis plants were established in a Cu contaminated sterilized soil and treated with the following: i) uninoculated (-M); ii) inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…This accumulation response has been widely observed in other plant species such as Chloris gayana , Cucumis sativum and some Eucalyptus species exposed to Cu, in which higher Cu accumulation in root than shoot is probably due to a fast absorption by the roots and its slow translocation to shoot [ 31 ]. Moreover, this behavior is similar to other species that cohabit with I. cylindrica in the Cu-ontaminated environment from Puchuncaví Valley, as Oenothera picensis [ 8 , 32 , 33 , 34 ]. Also, previous studies have shown how I. cylindrica inhabits soils with more than 300 mg kg −1 of Cu available [ 8 ] and how its accumulating capacity in the root increases according to the amount of Cu applied to the soil, at least between a range of 450–780 mg kg −1 of Cu in soil [ 35 ].…”
Section: Discussionsupporting
confidence: 71%
“…This accumulation response has been widely observed in other plant species such as Chloris gayana , Cucumis sativum and some Eucalyptus species exposed to Cu, in which higher Cu accumulation in root than shoot is probably due to a fast absorption by the roots and its slow translocation to shoot [ 31 ]. Moreover, this behavior is similar to other species that cohabit with I. cylindrica in the Cu-ontaminated environment from Puchuncaví Valley, as Oenothera picensis [ 8 , 32 , 33 , 34 ]. Also, previous studies have shown how I. cylindrica inhabits soils with more than 300 mg kg −1 of Cu available [ 8 ] and how its accumulating capacity in the root increases according to the amount of Cu applied to the soil, at least between a range of 450–780 mg kg −1 of Cu in soil [ 35 ].…”
Section: Discussionsupporting
confidence: 71%
“…It is noteworthy that in situations of abiotic stress, the isolated Cc has previously been shown to be highly efficient in increasing plant biomass growing in contaminated soils, related to a high colonization and densities of propagules (Meier et al 2015), an increased production of glomalin and also accumulating high amounts of Cu in spores (Cornejo et al 2017), which together may act as a symbiotic rhizosphere barrier to the entry of phytotoxic ions to host roots, Na + in this case. This aspect has been previously studied, suggesting that the AMF acts as a primary barrier to Na + ions when they reach toxic levels, by increasing the concentration in the root and decreasing its translocation towards the shoot.…”
Section: Discussionmentioning
confidence: 99%
“…Soil fungal communities are crucial for ecosystem functioning and strongly drive abiotic soil conditions (van der Heijden et al, 2008;Aguilera et al, 2017;Cornejo et al, 2017). Vice versa, fungal assemblages are dependent on soil physicochemical conditions, plant nutritional status, and plant community composition (Lauber et al, 2008).…”
Section: Introductionmentioning
confidence: 99%